2016
DOI: 10.4236/jep.2016.75057
|View full text |Cite
|
Sign up to set email alerts
|

Contaminant Properties of Hospital Clinical Laboratory Wastewater: A Physiochemical and Microbiological Assessment

Abstract: Hospital laboratory wastewater has been considered to significantly change the degree of contamination of especially the hospital wastewater. The present study investigated the hospital clinical laboratory wastewater and the pollution loads were assessed for pathogens, heavy metals, and organic materials. Composite samples were collected from clinical laboratory wastewater of a 350-bed hospital for a six-month period. Analyses for pH, TSS (Total Suspended Solid), BOD (Biochemical Oxygen Demand), COD (Chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The effluent from hospitals is directly discharged into the municipal sewer system co-treated with urban wastewater. HWW poses a grave risk to humans as it radically disseminates infectious pathogens found in healthcare wards to the environment 18 . The dissemination of antibiotic non-susceptible bacteria, their reservoirs and distribution in the environment are very pertinent issues.…”
Section: Discussionmentioning
confidence: 99%
“…The effluent from hospitals is directly discharged into the municipal sewer system co-treated with urban wastewater. HWW poses a grave risk to humans as it radically disseminates infectious pathogens found in healthcare wards to the environment 18 . The dissemination of antibiotic non-susceptible bacteria, their reservoirs and distribution in the environment are very pertinent issues.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 , 16 The number of coliforms released from hospital mostly depends on the number of patients served, hospital capacity, and the type of case-managed. 23 During the diagnosis and treatment of disease, the hospital releases large amounts of pathogenic bacteria. 23 At the same time hospital could be a storm house of ARB due to the large use of antibiotics to treat bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…23 During the diagnosis and treatment of disease, the hospital releases large amounts of pathogenic bacteria. 23 At the same time hospital could be a storm house of ARB due to the large use of antibiotics to treat bacterial infections. 24 Almost all studies showed the presence of pathogenic bacterial isolates such as klebsiella spp., E. coli, P. aeruginosa, S. aureus, and Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of antibiotics used in human and animal healthcare is partially metabolized and released through excreta into the municipal sewage system. Untreated liquid waste containing partially metabolized antibiotics in low concentration contributes largely to the development of antibiotic resistance in the environmental microflora [ 2 5 ]. If hospitals and municipal sewage effluents are not treated, infectious agents and antibiotic-resistant microbes are shed into rivers and finally reach into communities.…”
Section: Introductionmentioning
confidence: 99%